The impact of environmental knowledge, green word of mouth and green marketing on green purchase intention with environmental attitude as a mediating variable - Julia Azizah, Viola; Dwita, Vidyarini (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of environmental knowledge, green word of mouth and green marketing on green purchase intention with environmental attitude as a mediating variable in Avoskin Skincare in Padang City. The sampling technique used purposive sampling. The research participants totaled 190 respondents who were selected as samples. Analysis using PLS 4.0 software shows that environmental knowledge, green word of mouth and green purchase intention significantly affect environmental attitude and green purchase intention. Environmental attitude mediates the relationship between environmental knowledge, green word of mouth and green purchase intention and environmental attitude does not mediate the relationship between green marketing and green purchase intention.